Towards a rules-based community : an ASEAN legal service / Jean-Claude Piris and Walter Woon. - Piris, Jean-Claude; Woon, Walter C. M. (Integration through law (Cambridge, England), 2015)
In 2007, ASEAN adopted the ASEAN Charter, which stated its ambition to become a 'rules-based' community respecting the rule of law. In order to fulfil this objective, it is vital that the necessary legal infrastructure has effective legal support. This book helps readers to understand the need for and role of such a legal service. To begin with, it explores the way ASEAN and its various institutions have evolved. The current situation with respect to the making of rules and settlement of disputes is then analysed, drawing not only on published primary and secondary materials, but also on the experience of diplomats, officials and legal officers. Finally, the authors draw on their practical experiences, as former attorney-general of an ASEAN member state and former head of the European Council legal service, to make recommendations on how an ASEAN Legal Service might be organised.